Circulating microparticles from diabetic rats impair endothelial function and regulate endothelial protein expression. (20th August 2015) - Ishida, K.; Taguchi, K.; Hida, M.; Watanabe, S.; Kawano, K.; Matsumoto, T.; Hattori, Y.; Kobayashi, T.
Abstract: Aim: Diabetes mellitus increases the risk of cardiovascular disease, which is accompanied by functional and structural changes in the vascular system. Microparticles (MPs) have been described as biological vectors of endothelial dysfunction in other pathologies. However, the molecular mechanisms underlying their formation and signalling are unclear. We investigated the role of MPs derived from streptozotocin (STZ)‐induced diabetic rats in endothelial function. Methods: Male Wistar rats were injected with STZ to induce diabetes, and MPs isolated from control or STZ‐induced diabetic rats were characterized by dot blotting (assessed by CD62P detections), flow cytometry (assessed by annexin V detections) and ELISA. Carotid arteries from rats were incubated with MPs, and expressions of enzymes and endothelium‐dependent relaxation were analysed. Results: The circulating levels of MPs, particularly the levels of platelet‐derived microparticles, from diabetic rats were higher than those present in controls. Endothelium‐dependent relaxation induced by acetylcholine (ACh) was attenuated in carotid arteries from STZ‐induced diabetic rats. Following the incubation of control carotid arteries with MPs isolated from STZ rats, ACh‐induced endothelium‐dependent relaxation was impaired, but MPs isolated from control rats had no such effect. Furthermore, the effect of MPs was mediated by a decrease in expression of endothelial nitric oxide synthase (eNOS) and the overexpression of caveolin‐1. Conclusion: Circulating MPs isolated from STZ‐induced diabetic rats induce endothelial dysfunction in carotid arteries and regulate protein expressions of eNOS and caveolin‐1. These data advance our understanding of the deleterious effects of circulating MPs observed in disorders with diabetic complications.